2018
DOI: 10.1016/j.snb.2018.02.159
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flow test for visual detection of multiple MicroRNAs

Abstract: The authors describe a rapid and low-cost approach for multiplex microRNA(miRNA) assay on lateral flow nucleic acid biosensor (LFNAB). The principle of assay is based on sandwich-type nucleic acid hybridization reactions to produce gold nanoparticle (GNP)-attached complexes (ssDNA-microRNA-ssDNA/GNPs), which are captured and visualized on the test zone of LFNAB. By designing three different test zones on LFNAB, simultaneous detection of microRNA-21, microRNA-155 and microRNA-210 was achieved with an adding-mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…Up to now, no perfect method can overcome all shortcomings. However, probe-based lateral flow assay in combination with SDA could provide robust multiplexing detection higher than their peer antibodies [84]. For example, our group [15,24,36] and other researchers [3,100,101] demonstrated that SDA can be used to amplify short target recognition sequences, for example, aptamers, after target binding and then integrated with lateral flow biosensors for analysis.…”
Section: Discussion Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, no perfect method can overcome all shortcomings. However, probe-based lateral flow assay in combination with SDA could provide robust multiplexing detection higher than their peer antibodies [84]. For example, our group [15,24,36] and other researchers [3,100,101] demonstrated that SDA can be used to amplify short target recognition sequences, for example, aptamers, after target binding and then integrated with lateral flow biosensors for analysis.…”
Section: Discussion Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Lateral flow biosensor is the most commonly used technology for the point of care testing [81][82][83][84]. A test strip consists of four parts: a sample pad, a conjugate pad, a nitrocellulose membrane, and an absorption pad.…”
Section: Lateral Flow Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…S13 and Table 1). However, there was not any signal in either test zone or control zone when 50 μL of pure serum samples with miR-210 mimic (up to 50 pmol) was loaded with direct sampling method, possibly because the binding ability between nucleotides is poor in pure serum on the condition that the sample pad has not been pre-treated by buffer solution before usage 31 . In both sandwich-like and competitive formats, LODs obtained by pre-enrichment at 1:1 dilution were equivalent to those obtained in running buffers, indicating that the proposed test-zone pre-enrichment sampling strategy had promising analytical applications in real biological samples.…”
Section: Analysis Of Mock Clinical Samplesmentioning
confidence: 99%
“…In light of this, numerous groups have developed strip-based biosensors for miRNA detection (Hou et al, 2012;Gao et al, 2014;Deng et al, 2017a). Given most medical diagnoses are made after testing a panel of two or more biomarkers, Zheng et al (2018) developed a multiplexed lateral flow assay for the simultaneous detection of miR-21, miR-155 and miR-210 in human serum samples at concentrations as low as 68, 7, and 17 pM, respectively, within 10 min ( Figure 3A). Deng et al (2017a) sought to overcome the limited sensitivity of previous lateral flow based biosensors by incorporating a target recycling amplification strategy, whereby two sequence specific hairpins are used to amplify the signal without the need for added enzymes.…”
Section: New and Emerging Mirna Detection Platformsmentioning
confidence: 99%